Recent advances and future research in ecological stoichiometry - Sardans, J.; Janssens, Ivan A.; Ciais, Philippe; Obersteiner, Michael; Peñuelas, J. (Perspectives in plant ecology, evolution and systematics, 2021)
•Ecological stoichiometry (ES) studies have growth exponentially in the last years.•ES studies have advanced relating elemental composition with several ecosystem traits.•Biogeochemical niche hypothesis is linking elemental composition with species niche.•The drivers of global change are beyond a general imbalance of ecosystems N:P ratio.•We identify future ES research in the frame of ecosystem function and global change. Studies on ecological stoichiometry (ES) have increased rapidly in number in recent years. Continuous exploration of classical concepts such as the growth-rate hypothesis (GRH),), which is based on the relationship between the nitrogen:phosphorus (N:P) ratio of organisms and their growth-rate capacity, has identified new patterns and uncertainties, particularly with regard to terrestrial plants and microbial systems. Another concept that has proven to be helpful is the Redfield ratio, which postulates a consistent carbon:nitrogen:phosphorus (C:N:P) molar ratio of 100:16:1 in marine phytoplankton and open oceanic waters, and this ratio is related to the protein:rRNA ratio associated with protein synthesis. ES studies in all types of ecosystems have demonstrated that shifts in the elemental composition of water, soil, organisms, and communities are linked to the spatiotemporal structure and function of the ecosystem communities. The recent trend of also considering additional bio-elements such as potassium (K), magnesium (Mg) and calcium (Ca), has improved our understanding of how resource availability in complex ecosystems affects basic organism functions such as growth, stress responses, and defensive mechanisms. The biogeochemical or bio-elemental niche hypothesis is a novel tool that uses the concentrations and ratios of several bio-elements to define species niches and to scale up processes at the community and ecosystem levels. Global environmental changes, such as an increase in atmospheric CO2, drought, N deposition, and species invasion, change the elemental composition of the growth media (soil and water), organisms, and ecosystems. For example, the growing imbalance between N and P that results from very large anthropogenic inputs of reactive N and smaller inputs of P into the biosphere is increasingly affecting the health of both ecosystems and humans. In this review, we summarise recent advances in ecological stoichiometry and identify key questions for future research on the impacts of ES on ecosystem function and structure due to global environmental change.